The relationship between the level of knowledge, parental attitudes and accessibility of health services with compliance in providing complete basic immunization to infants at Posyandu Mawar, Makarti Jaya District, Banyuasin - sari, Sari; Rizki Amalia; Rini Gustina Sari; Intan Sari (SEKOLAH TINGGI ILMU KESEHATAN INDRAMAYU, 2025)
Immunization is a way to prevent infectious diseases, especially diseases that can be prevented by immunization (PD31), low immunization coverage in infants can inhibit the formation of immunity and has the potential to cause disease outbreaks. The purpose of this study was to determine the relationship between the level of knowledge, parental attitudes and accessibility of health services with compliance in providing complete basic immunization to infants. This type of research was quantitative with a cross-sectional approach. The population of the study were all mothers who had 9-month-old babies who visited Posyandu Mawar in January-July, totaling 56 respondents. Sampling used total sampling technique. The results of univariate analysis were obtained from 56 respondents who were compliant in providing complete basic immunization. as many as 26 respondents (46.4%), respondents with a good level of knowledge were 27 respondents (48.2%), respondents with a positive attitude were 23 respondents (41.1%), respondents who had easy accessibility to health services were 23 respondents (41.1%). Based on the results of the study using the chi-square statistical test, the variable level of knowledge P value was 0.034 (a => 0.05), parental attitudes obtained a p value of 0.037 (a => 0.05), accessibility of health services obtained a p value of 0.009 (a =>0.05). The conclusion that there was a relationship between the level of knowledge, parental attitudes and accessibility of health services simultaneously with compliance in providing complete basic immunization to infants at Posyandu Mawar, Makarti Jaya District, Banyuasin Regency. Suggestions for posyandu workers in improving immunization compliance at Posyandu Mawar by conducting intensive socialization to parents, involving the community, and giving awards for families who comply with the immunization schedule so that they can create a healthier generation at Posyandu Mawar.